Evaluation of receiving ability of teenage male table tennis players in Taiwan - Liu, Y.-T.; Chiou, C.-C.; Chen, J.-L.; Tang, C.-Y. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to evaluate the forehand rmiving ability of teenage male table tennis players. Thirty-nine male players consist of skill levels from junior to senior high school students and national squads were selected. This assessment involves three tests: basic control, judgment, and match-like condition simulation. We found under the basic control test, the junior high school players performed poorer in downspin and left-side downspin in the aspect of accuracy (P<0.01). As for the judgment test, the junior high school players showed less accuracy in all kinds of backspin typs, compared to national squads level players (P<0.01). In the test of match-like condition simulation, Junior high school players showed that their ability in handling all kind of spins to be relatively weak compared to senior high school and national level players.